Implementation of Problem Based Learning Model Assisted by Video Media in Science Learning for Grade IV Elementary School Students - Fela Novita; Dodik Mulyono; Dea Widaswari (CV. Edujavare Publishing, 2026)
Every human being has the same right to education and hopes to always thrive in education. This study aims to determine the achievement of social studies learning outcomes of grade IV students of SD Negeri 46 Lubuklinggau after the implementation of the Problem Based Learning (PBL) learning model assisted by Vidio media. This study uses a Quantitative Approach with an experimental research method in the form of One Group Pre-test Pos-test design. The subjects in this study are grade IV students of SD Negeri 46 Lubuklinggau for the 2025/2026 school year. The results showed that the average score of the Pre-test was 28 with a standard deviation of 6.14 while the average score of the Post-test was 80.54 with a standard deviation of 5.18. The normalistic test showed that the pre-test data and the post-test data were mormalally distributed because the value χ_(count )^2 was less than χ_(table )^2 which was 1.3173 < 11.07. Furthermore, the analysis using the t-test at a significant level of α= 0.05 showed that t_(calculate=)7.11> t_tabel = 1.64 so that H_oditolak and H_a were accepted. Thus, it can be concluded that the application of the Problem Based Learning learning model assisted by Video Media can significantly improve the learning outcomes of IPAS students in grade IV of SD Negeri 46 Lubuklinggau and achieve learning completeness with a score category of ≥ 73.